Sprint performance and force-velocity profiling does not differ between artificial turf and concrete. Issue 4 (August 2021) - Shahab, Samad; Steendahl, Ida B; Ruf, Ludwig; Meyer, Tim; Van Hooren, Bas
Purpose: Force-velocity-power (F-v-P) profiling can illustrate an individual's sprinting capabilities, but no study has explored the effect of different running surfaces on F-v-P outcomes. Method: Twelve elite youth football players (age 16.3 ± 0.5 years, mass 67.3 ± 5.4 kg, height 176.2 ± 4.6 cm) performed two 30 m sprints on concrete and artificial turf in a randomised order on two testing days. Differences between surfaces were determined using repeated-measures ANOVA (P < 0.05), whilst the coefficient of variation (CV), smallest worthwhile change and standard error of measurement were calculated to quantify reliability. Results: No significant differences were found between surfaces over the average of two days. High reliability was evident for 30 m sprint time, theoretical maximum horizontal velocity and ratio of force on both surfaces (CV≤∼5%), while the remaining outputs were not reliable (CV >10%). Conclusion: These findings show that F-v-P profiling does not differ between concrete and artificial turf. However, higher variability on the more unfamiliar concrete surface suggests that the testing surface should match the playing surface. Since the standard error of measurement is larger than the smallest worthwhile change, the ability of this method to monitor seasonal changes may be limited in youth elite soccer players.